Social Networks in Limbo. The Experiences of Older Adults During COVID-19 in Ghana - Asante, Emmanuel Akwasi; Awuviry-Newton, Kofi; Abekah-Carter, Kwamina (Frontiers in Public Health, 2021)
While studies exploring COVID-19 and its global influence have begun, social networks and support among older adults in low-and middle-income countries, such as Ghana have been inadequate despite its enormous relevance. Thus, the study presents the voices of older adults in Jamestown, Accra and their social networks during the COVID-19 pandemic in Ghana. Using a phenomenological approach, data were collected from 15 older adults through in-depth interviews on older adults' social network experiences during COVID-19 pandemic situation. Older adults generally struggled to maintain connections with their family members, friends, neighbors, and the community, especially during the lockdown. They ascribed their limited interaction to COVID-19 preventive measures, such as social distancing and the limitation of face-to-face meetings imposed by the government. Loneliness, stress, and depression are also linked to the breakdown of social networks. The findings provide a deeper understanding of the impact of COVID-19 on older adults' quality of life. It emerged that the Ghanaian society could reconsider the professional services of gerontologists, social workers, community outreach workers, and philanthropists in mitigating loneliness, stress, and depression among older adults in current and future pandemics.